(untitled) (Research, Society and Development, 2022)
Objective: To describe information on cuff pressure, used in intubated patients, as a preventive measure related to bronchoaspiration and the development of ventilator-associated pneumonia (VAP). Methodology: This is an integrative literature review, carried out in the SCOPUS® and MEDLINE® databases. The eligibility criteria used were studies published between 2010 and 2021, with full text available, such as retrospective, prospective, cohort, observational, pilot study, multicenter randomized study and systematic review. Duplicate studies and publications without the full text available were excluded from the selection process. Results: 11 studies met the eligibility criteria and were presented in a descriptive manner. It was found that the measurement of cuff pressure proved to be a safe way to manipulate the oral cavity and that continuous cuff control contributed to the prevention and reduction of complications such as bronchoaspiration and ventilator-associated pneumonia. In addition, control of cuff pressure with lumen for drainage of subglottic secretion may help prevent VAP in patients who require more than 48 hours of mechanical ventilation. Final considerations: care with cuff pressure of endotracheal tubes is of fundamental importance in reducing infections in critically ill patients, such as pneumonia associated with mechanical ventilation. In addition, monitoring cuff pressure, as a prophylactic method, becomes essential in the protocol routine of the multidisciplinary team of Intensive Care Units and can be performed by any trained member, including the dentist.